2018
DOI: 10.1111/epi.14497
|View full text |Cite
|
Sign up to set email alerts
|

Status epilepticus in the elderly

Abstract: Children and the elderly (≥60 years of age) have the highest incidence of status epilepticus (SE). Because of their general health, elderly individuals are much more likely than younger (<60 years of age) persons to have more severe consequences from seizures. The incidence of SE is 15.5/100 000 in the 60-69 age group, 21.5/100 000 in the 70-79 age group and 25.9/100 000 in persons 80 and older. The most common cause in the elderly is acute symptomatic, with stroke and hypoxia the most frequent. The overall mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 17 publications
1
18
1
2
Order By: Relevance
“…Alcohol- and stroke-related cases of SE were less common in our study than in an article by Leppik (19). He found stroke to have caused 52.3% of the cases of SE among the elderly adults and 17.7% in middle-aged adults, while, in our study, the figures were 16.3 and 7.4%, respectively.…”
Section: Discussioncontrasting
confidence: 73%
“…Alcohol- and stroke-related cases of SE were less common in our study than in an article by Leppik (19). He found stroke to have caused 52.3% of the cases of SE among the elderly adults and 17.7% in middle-aged adults, while, in our study, the figures were 16.3 and 7.4%, respectively.…”
Section: Discussioncontrasting
confidence: 73%
“…The mean annual incidence of SE in the elderly ranges between 15.5/100,000 and 25.9/100,000 ( 42 ), with the most common cause being acute symptomatic seizures related to vascular events or brain hypoxia ( 42 ). We found that 4% of elderly patients with new onset seizures presented in status epilepticus, with an epileptogenic lesion detected in all of those patients.…”
Section: Discussionmentioning
confidence: 99%
“…24 The mortality rate associated with SE varies with age, and is approximately 50% among individuals aged >80 years. 25…”
Section: Diagnosis: Different Clinical Manifestations In Elderly Patimentioning
confidence: 99%